1998
DOI: 10.1042/bj3300047
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of the interleukin 6 signal transducer gp130 does not require activation of the Jak/STAT pathway

Abstract: Signalling receptors often undergo receptor-mediated endocytosis. In many cases this internalization is stimulated by ligand binding and activation of intrinsic receptor tyrosine kinases, resulting in a receptor down-regulation. We have analysed whether internalization of the interleukin 6 signal transducer gp130 is dependent on the activation of receptor-associated Jak kinases. By using a chimaeric receptor system we found that receptor mutants that lack box1 and therefore are not capable of activating Jak an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 41 publications
8
40
0
Order By: Relevance
“…These results suggest that the dileucine motif is required for IL-13-IL-13R␣2 chain complex internalization. Thus, our results confirm previous observations that the dileucine motif is necessary for internalization of various cytokine-receptor complexes (22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results suggest that the dileucine motif is required for IL-13-IL-13R␣2 chain complex internalization. Thus, our results confirm previous observations that the dileucine motif is necessary for internalization of various cytokine-receptor complexes (22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Discussionsupporting
confidence: 82%
“…It has been demonstrated that a dileucine motif in the intracellular domain of various receptor systems (e.g. interleukin-6 receptor (IL-6R) gp130, granulocyte colony-stimulating factor receptor, epidermal growth factor receptor, growth hormone receptor, human insulin receptor, ␤ 2 -adrenergic receptor, lutropin/choriogonadotropin receptor, and erythropoietin receptor) plays an essential role in the internalization of ligand (22)(23)(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…The list so far includes: TGF-a, TNF-a, IL-6, EGF, and insulin (all in rat hepatocytes), growth hormone and insulin (in cirrhotic patients), and glucagon (in isolated rat liver plasma membranes) (Table 3) [10,18,62,63,71,91,99]. Remarkably, most of these molecules are known to be internalized by clathrinmediated endocytosis [8,9,23,61,73,80,88,103,105,109]. At present, it is not well established whether the impaired internalization of these various ligands requires ethanol metabolism, but based on the receptor defects described earlier, the prediction is that it does.…”
Section: Cytokines Growth Factors and Hormonesmentioning
confidence: 99%
“…After p27 detection blots were stripped and hybridized with a GAPDH cDNA probe. Fold increase of p27 mRNA normalized according to GAPDH values was calculated using the ImageQuant software after scanning of the blots with a PhosphorImager (Molecular Dynamics) of gp130 (Dittrich et al, 1996;Thiel et al, 1998) and which may account for the lower surface expression of the full-length EG construct compared to the shorter constructs (Figure 3). Studies are in progress to answer this question.…”
Section: Growth Inhibition Of Melanoma Cells By Il-6-type Cytokines Dmentioning
confidence: 99%